Treatment of Batik Wastewater using Recycled Coagulants from GWTPS (Ground Water Treatment Plant Sludge) - Abu Bakar, Ahmad Solihin (IRC, 2019)
Industrial Batik production is very well known in East Coast of Peninsular Malaysia especially in Terengganu and Kelantan and in some part of other states in Malaysia such as Perak. This industry traditionally inherited from generation to generation that make big contribution to economic growth due to high demand locally and abroad. However, the industry produces wastewater which contributes to water pollution since it utilizes a lot of chemicals. Preliminary study of the Batik Wastewater contains high reading of Colour and COD that is dangerous to human and aquatic life